Challenges of budgetary control system and its impact in management performance in local government authorities in Tanzania: Case study of Kisarawe district council (KDC) - Kilangaly, Alex N. (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University, Dar es Salaam Campus College in partial fulfillment of the requirements for the award of Master Degree in Accounting and Finance (MSc-A&F).